Culture, assumptions about the world, and interpretations of children's disabilities - Chen, Fan Xuan (2022)
Sim et al. (2021) examined the interplay between parental caretakers and children with health disabilities in East Asian cultures. Their analyses suggested that the way East Asian mothers responded to their disabled children may have to do with the culture in which they were embedded. Complementing their work, we aim to integrate their findings with the cultural psychology literature, focusing on styles of thought and supernatural beliefs. Doing so allows us to forge theoretical links between Sim et al. (2021) and frameworks that delineate the distinct ways of thought in East Asian cultures, recommend promising directions for future research, and motivate interdisciplinary readership.